Does summer irrigation alter nitrogen uptake and utilisation efficiency of saffron (Crocus sativus L.) for different organic and chemical fertilisers?. Issue 13 (10th November 2021) - Bicharanloo, Bahareh; Moghaddam, Parviz Rezvani; Asadi, Ghorbanali
ABSTRACT: Nutrient loss is one of the most important problems in saffron cultivation which affects saffron production. Summer irrigation during flower initiation period improves saffron yield but affects nutrient availability. This study aimed to evaluate the role of summer irrigation on saffron nitrogen (N) uptake and utilisation efficiency for different organic and chemical fertilisers. A three-year field experiment was conducted as split-plot under a randomised complete block design with three replications. Main plots were included the summer irrigation and no-summer irrigation, subdivided to five sub-plots including chemical fertiliser, vermicompost, cow manure, chicken manure, and control. The measured criteria were corm N concentration, N uptake efficiency (NUpE), N utilisation efficiency (NUtE), agronomic N use efficiency (AgNUE) and saffron corm and flower yield parameters. The results revealed that organic manures improved corm NUpE, NUtE and AgNUE. Plants had the highest NUpE under cow manure and utilised N more efficiently, resulted in the highest NUtE and AgNUE. Summer irrigation had implications for different organic fertilisers with a positive effect on vermicompost but a negative effect on chicken manure and chemical fertiliser. Dry stigma and corm yield were higher in vermicompost than chicken manure under summer irrigation, while it decreased with chemical fertilisation.